MOOCs as Change Agents to Boost Innovation in Higher Education Learning Arenas - Ebba Ossiannilsson; Fahriye Altinay; Zehra Altinay (MDPI AG, 2016)
Massive open online courses (MOOCs) provide opportunities for learners to benefit from initiatives that are promoted by prestigious universities worldwide. The introduction of MOOCs in 2008 has since then transformed education globally. Consequently, MOOCs should be acknowledged as a pedagogical innovation and recognized as change agents and facilitators in the transition of opening up education, in the transition from traditional campus education to open online learning arenas, which increases learners' access to and equity in lifelong learning. There is a need to consider MOOCs as a natural part of universities' course offerings and business models and to recognize MOOCs as valuable for learners. Furthermore, MOOCs should be regarded as valuable learning and educational initiatives in the same way that journals and books are recognized. Learners should be able to take MOOCs either at their own university or from other providers. Moreover, MOOCs should be valued in policies, strategies, and action plans, and they should be included in processes of quality enhancement and quality assurance. This paper points out the merits of the innovative use of MOOCs in higher education. In this qualitative literature research, a content method analysis was conducted through a systematic review of the literature. Through the findings from the literature research it is suggested that MOOCs could be permanent change agents that boost innovation in higher education learning arenas. In particular, the findings revealed the benefits of MOOCs in various areas, such as lifelong learning, professional competence development, validation of learning, and degree recognition, in addition to clarifying several business models of higher education.